Decades of research in drug targeting using gastroretentive drug delivery systems for antihypertensive therapy - Amit Porwal; Harinath Dwivedi; Kamla Pathak (Universidade de São Paulo, 2017)
ABSTRACT The limitations in absorption of drugs with narrow absorption window, or those unstable in the intestinal pH or those exhibiting low solubility at high pH are primary candidates for gastroretentive drug delivery systems (GRDDS). The delivery system has been widely explored for its commercial potential for a wide variety of therapeutic agents. GRDDS offer clinical therapeutics for acute and chronic management. Hypertension is a chronic disease that requires long term treatment and its management by patient compliant dosage forms would be clinically useful. Antihypertensives belonging to different classes have proved good candidates for the formulation of GRDDS. The review aims to discuss various GRDDS researched for antihypertensive drugs to increase the gastric residing time, bioavailability, henceforth to reduce the dose of the drug, dosing frequency and increase patient compliance. It also explores various marketed products and the patents filed/granted for GRRDS of antihypertensives. The GRDDS investigated include effervescent and non-effervescent floating drug delivery systems, swelling and expanding systems and bio/mucoadhesive systems. Many other systems that provided research platforms include high density systems, raft forming systems and osmotic delivery systems. In clinical context, wherein combination of antihypertensives is indicated, dual release delivery systems may also be explored.